ART EMPOWERMENT USING PHOTOGRAPHY AND VITALITY RECONSTRUCTION OF RURAL PUBLIC CULTURAL SPACES——A CASE STUDY OF JIANGSU, ZHEJIANG AND SHANGHAI REGIONS - Wang, Chen; Wang-Edwards, Anita (Veredas do Direito, 2026)
Against the background of rural revitalization and the "Enriching the Countryside with Literature and Art" policy, rural public cultural spaces face insufficient vitality. Taking Jiangsu, Zhejiang and Shanghai as cases, this paper explores how photography art empowers the vitality of these spaces, analyzes their current status and dilemmas, summarizes empowerment mechanisms, and puts forward targeted paths to provide references for related practice and policy implementation.